Optimalisasi Jumlah Unit Rumah Tiap Tipe Sesuai Kemampuan Daya Beli Masyarakat - Endah Widiastuti (Lambung Mangkurat University Press, 2023)
This population growth has an impact on the economy and the community's need for housing. This is an opportunity for developers to open residential areas. Developers need to pay attention to the purchasing power of the people so that housing is built optimally and developers can generate maximum profits. Research was conducted to find the optimal combination of the number of houses for each type. These limitations include limits on production costs, limits on land area, limits on construction time, and limits on people's purchasing power for each type of house. This study uses the QM for Windows program to process the data analysis. The primary data used was obtained from 50 questionnaires distributed and the secondary data was obtained based on the developer's information. The optimization results obtained are 45 units of subsidized type 36 houses, 51 units of non-subsidized type 36 houses, 39 units of type 45 houses, and 15 units of Type 50 houses. The developer generates a maximum profit of IDR 8,534,000,000.00 with a total of 150 houses built. Sensitivity analysis was also carried out on the purchasing power of the people. The result is that people's purchasing power has a major influence on the combination of the number of houses of each type that are built and the benefits that the developer gets.